2022
DOI: 10.1038/s41590-022-01325-9
|View full text |Cite
|
Sign up to set email alerts
|

CMTM4 is a subunit of the IL-17 receptor and mediates autoimmune pathology

Abstract: Interleukin-17A (IL-17A) is a key mediator of protective immunity to yeast and bacterial infections but also drives the pathogenesis of several autoimmune diseases, such as psoriasis or psoriatic arthritis. Here we show that the tetra-transmembrane protein CMTM4 is a subunit of the IL-17 receptor (IL-17R). CMTM4 constitutively associated with IL-17R subunit C to mediate its stability, glycosylation and plasma membrane localization. Both mouse and human cell lines deficient in CMTM4 were largely unresponsive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…CMTM6 and CMTM4 reduce the ubiquitylation of PD-L1 and increase its protein half-life, which affects tumor immune responses [ 22 , 23 ]. CMTM4 is also identified as a component of IL-17R and mediates autoimmune diseases [ 24 ]. This work characterizes a new role of CMTM3 as an immunity regulator during H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMTM6 and CMTM4 reduce the ubiquitylation of PD-L1 and increase its protein half-life, which affects tumor immune responses [ 22 , 23 ]. CMTM4 is also identified as a component of IL-17R and mediates autoimmune diseases [ 24 ]. This work characterizes a new role of CMTM3 as an immunity regulator during H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some CMTM family members are immunity regulators [22][23][24]. H. pylori induces IL-8 expression in gastric epithelial cells, which is an important source of IL-8 [25].…”
Section: Cmtm3 Promotes Il-8 Production and Inhibits Apoptosis Of Gas...mentioning
confidence: 99%
“…Knizkova and colleagues identified a new adaptor molecule involved in the IL‐17/IL‐17R cascade 3 . Through murine and human cell models, the authors found that CMTM4 (CKLF like MARVEL transmembrane domain containing 4) constitutively bound to the subunit IL‐17RC becoming integral part of the IL‐17R signaling complex (IL‐17RSC) upon IL‐17A stimulation.…”
Section: Figurementioning
confidence: 99%
“…volved in the IL-17/IL-17R cascade. 3 Through murine and human cell models, the authors found that CMTM4 (CKLF like MARVEL transmembrane domain containing 4) constitutively bound to the subunit IL-17RC becoming integral part of the IL-17R signaling complex (IL-17RSC) upon IL-17A stimulation. CMTM4 promoted the surface expression of IL-17RC by regulating posttranslational modifications, especially IL-17RC glycosylation and trafficking to trans-Golgi up to plasma membrane.…”
Section: Knizkova and Colleagues Identified A New Adaptor Molecule In-mentioning
confidence: 99%
See 1 more Smart Citation